2021
DOI: 10.1142/s0218348x22500281
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Permeability Model in Damaged Tree-Like Bifurcating Networks Considering the Influence of Roughness

Abstract: The seepage in tree-like bifurcating networks is a very common phenomenon in nature. The research on the transport characteristics of tree-like bifurcating networks has always been a hot topic. In this paper, a novel permeability model for fluid flow in damaged tree-like bifurcating networks is proposed. In the proposed model, the influence of roughness on permeability is considered by means of the fractal method. It is found that the permeability is not only related to the structural parameters of the network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Nowadays, tree-like bifurcation network structures have been widely used in the field of characterization of porous media. Zhang and Xiao et al studied the heat conduction of asymmetric and damaged tree-like bifurcation networks embedded in porous media. , Liu et al, based on the tree-like bifurcation network structure, found that the permeability of the porous media was related to the damaged position and the number of damaged tubes at the damaged position and established a new permeability model . Liu et al used a tree-like bifurcation network to characterize the internal fracture network morphology of the coal body and established a seepage model for the fracture network of the water-injected coal body .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, tree-like bifurcation network structures have been widely used in the field of characterization of porous media. Zhang and Xiao et al studied the heat conduction of asymmetric and damaged tree-like bifurcation networks embedded in porous media. , Liu et al, based on the tree-like bifurcation network structure, found that the permeability of the porous media was related to the damaged position and the number of damaged tubes at the damaged position and established a new permeability model . Liu et al used a tree-like bifurcation network to characterize the internal fracture network morphology of the coal body and established a seepage model for the fracture network of the water-injected coal body .…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 Liu et al, based on the tree-like bifurcation network structure, found that the permeability of the porous media was related to the damaged position and the number of damaged tubes at the damaged position and established a new permeability model. 13 Liu et al used a tree-like bifurcation network to characterize the internal fracture network morphology of the coal body and established a seepage model for the fracture network of the water-injected coal body. 14 Jin, Zhou, and He et al used gas adsorption experiments to determine the fractal characteristics of the pore structures of coal bodies and analyze the relationship among the fractal dimensions of pores.…”
Section: Introductionmentioning
confidence: 99%